MANAGEMENT AND MANUFACTURE OF BOTTLE WASTE WASHING MACHINE FOR PRODUCTION FACILITIES OF SME'S FOR RECYCLING PLASTIC WASTE PROCESSING IN LANGSA CITY - Suryaman, Nia Nuraeni (Jurnal Ilmiah Teknologi Infomasi Terapan, 2021)
Along with the development of technology, the need for plastic will continue to increase. The high population is certainly directly related to the large volume of waste generated. Therefore, the Directorate of IKM Region I took the initiative to facilitate IKM Plastic Waste Processing to be recycled in order to overcome environmental problems that are being faced by the Langsa City Regional Government. The purpose and objective of this activity is to procure machines/equipment that will be used as production facilities for the Recycled Plastic Waste Processing IKM in Langsa City. The research methodology is carried out in the form of implementation stages, namely 1) coordination and survey with related parties, 2) delivery, installation and testing, 3) handover of goods/works. The output of this research is 1 unit of bottle washer. The result of this research is to facilitate the IKM Production Facility for Recycling Plastic Waste Processing in Langsa City and it has been carried out according to the specifications and the time specified. The implementation of Machinery and Equipment/Facility Assistance activities is carried out in Sambas Regency, with the help of machinery/equipment facilities in the form of 1 unit of bottle washing machine.